2018
DOI: 10.1089/heq.2018.0015
|View full text |Cite
|
Sign up to set email alerts
|

The Beyond the Books Program: Improving Medical Student Attitudes Toward the Underserved

Abstract: Purpose: To determine the impact of the Beyond the Books (BTB) program, a short-term pre-clinical intervention, on medical student attitudes toward the underserved (MSATU).Methods: BTB was evaluated through a prospective cohort study using the validated MSATU questionnaire.Results: There were no significant MSATU total score differences between BTB students (n=13) and student controls (n=29) at the beginning of the program. At the program's conclusion, BTB participant MSATU total scores were significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…A total of 24 articles assessed the effectiveness of educational interventions [ 20 , 21 , 31 , 36 , 37 , 39 , 41 , 46 48 , 50 , 51 , 53 , 55 , 58 , 60 , 61 , 65 , 69 , 70 , 72 , 75 77 ]. Twenty were US studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 24 articles assessed the effectiveness of educational interventions [ 20 , 21 , 31 , 36 , 37 , 39 , 41 , 46 48 , 50 , 51 , 53 , 55 , 58 , 60 , 61 , 65 , 69 , 70 , 72 , 75 77 ]. Twenty were US studies.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen were controlled-group studies [ 20 , 21 , 36 , 37 , 46 , 47 , 49 , 50 , 60 , 61 , 59 , 70 , 72 ], among which two were randomized [ 46 , 60 ]. Five main types of educational interventions were evaluated: global curriculum dedicated to social accountability [ 20 , 21 , 36 , 46 , 47 , 48 , 50 , 51 , 53 , 60 , 61 , 72 , 77 ]; experiential community-based learning [ 37 , 41 , 70 ]; volunteering in student-run free clinics [ 55 , 58 , 69 , 76 ], traditional didactic learning ,, [ 31 , 39 , 65 ] and online curriculum [ 75 ]. Experiential community-based learning and global curricula showed the greatest positive impact on MS-ATU, whereas volunteering in student-run free clinics and traditional learning showed inconsistent results.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that service activities are correlated with higher levels of empathy, better understanding of community needs, and an increased belief that physicians have a responsibility to provide medical care for the needy [11][12][13][14][15]. Additionally, when studies specifically compare groups of students who participate in some type of community service to those that do not, results suggest that attitudes towards the underserved are consistently better in service groups [16][17][18][19]. The Liaison Committee on Medical Education has recognized the potential positive implications of service-learning and has added a mandate to their standards that medical schools "provide sufficient opportunities for, encourage, and support medical student participation in service-learning and/or community service activities" [20].…”
Section: Introductionmentioning
confidence: 99%
“…This finding may reflect their own perception of vulnerability and social instability or their previous experience with different governmental authorities, which increased their sensitivity towards disenfranchised populations [22]. In contrast, medical students who do not belong to minority groups or those who have limited contact with migrants from privileged backgrounds may not fully understand the needs of the vulnerable population [23].…”
Section: Discussionmentioning
confidence: 99%